Rajasthan rising a partnership for strong institutions and more livable cities. - Sharma, Manoj (Sustainable development working papers.)
Since 1998, the Rajasthan Urban Infrastructure Development Project (RUIDP) has undertaken extensive work to address urban challenges such as widespread poverty, inadequate infrastructure, and a harsh climate. This publication reflects on Rajasthan development issues and solutions and showcases how infrastructure investments and institutional support under the RUIDP have improved the economic conditions, health, and overall quality of life of citizens. It also discusses lessons learned and future priorities.